The Role of Marketing & Competitive Intelligence In Industrial Revolution 4.0 - Made Vera Kristanti Dewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2019)
ABSTRACT This study aims to examine the role of marketing and competitive intelligence in the industrial revolution 4.0, mapping the corporate strategy to be able to compete globally. This research use Grab as the research subject because of its ability to compete with Go-Jek in Indonesia particularly, and succeed in mastering Southeast Asia. The methodology was descriptive qualitative by using purposive sampling technique, interviewing several drivers and corporate grab partners (Managing Director of Grab Indonesia and Communication Manager Grab CEO's Office), observation, secondary data from several TV station interviews, and other publicly available data. The data analysis technique was data source triangulation (confirmatory) and theory triangulation. The results of this study indicates that Grab chose the expansion country by looking at the similarities that existed in the previous country, so that the duplication process could run easily, for example Grab Bike in Vietnam to be copied to Indonesian market. Grab understands to be accepted in a country, it has to understanding the needs of the country, because the needs are different in each country. To be able to compete with existing local products, the Hyperlocal and local partnership approach is carried out. Grab believes that only with approaches and local partnerships will make it easier to understand local needs and accelerate. To accelerate the development process, Grab has made a partnership with several companies that have the same goals. Grab's ability to adapt the changes will requires the right talent whom understand the context, and is supported by the right and mature technology. This research is expected to provide an overview of corporate strategy in entering global markets in the industrial era 4.0 by using competitive intelligence and marketing 4.0, and is able to compete with international companies. In the future, further research is expected to present a more in-depth analysis of marketing strategies as a form of corporate strategy implementation.